How Culture Influences the brand association in the United Kingdoms and Taiwan: a case study of L Oreal Paris. - Wang, Wei-Shien (2006)
Culture is one of the most influential factors in international marketing. This survey is designed to investigate the relationship between culture and consumers brand association in different countries by using L'Oreal Paris as a case study. Individualism and collectivism are used to be the measurement of culture. The United Kingdom and Taiwan are the representatives of these two cultures respectively. Setting hypotheses as consumers of the United Kingdom would put more emphasize on the non-product related attributes while consumers would pay more attention on the product related attributes in Taiwan.